A study for determination of various positioning errors in digital panoramic radiography for evaluation of diagnostic image quality - Apurva Mohite Khator; Mukta B Motwani; Anuraag B Choudhary (Wolters Kluwer Medknow Publications, 2017)
Faulty radiographs have poor diagnostic quality, and repetition of such poor-quality radiographs leads to increased patient exposure to radiation. Since digital panoramic radiography has replaced manual radiography, the only hindrance in producing good-quality radiographs is the positioning errors. Objectives: Our study aims to determine the various positioning errors and their relative frequency and to identify those errors directly responsible for diagnostically inadequate images. Materials and Methods: Five hundred panoramic radiographs taken serially (from the year 2007) were retrospectively assessed for the positioning errors by three oral and maxillofacial radiology specialists using a performa enlisting the errors. The three specialists had different duration of clinical experience and they evaluated the orthopantograms as diagnostically acceptable or unacceptable. They also observed the relative frequency of all the positioning errors. Statistical Analysis: The kappa value for intraobserver agreement was calculated, which suggested that the agreement among the observers was fair. Results: Of the 500 panoramic radiographs viewed by the three observers, 25 (5%) had no errors, while 475 (95%) showed one or more positioning errors. The most common error in our study was found to be head turned to one side (33.8%) and the least common error was patient movement during exposure (1.8%). Conclusion: Positioning errors are very common in digital panoramic radiography, and they lead to production of poor-quality radiographs. The operator should take this fact into consideration and spend more time in patient positioning, thereby reducing the repetition of radiographs and unwanted patient exposure.